2′-deoxy-ADPR activates human TRPM2 faster than ADPR and thereby induces higher currents at physiological Ca2+ concentrations - Pick, Jelena; Sander, Simon; Etzold, Stefanie; Rosche, Anette; Tidow, Henning; Guse, Andreas H.; Fliegert, Ralf (Frontiers in Immunology, 2024)
TRPM2 is a Ca 2+ permeable, non-selective cation channel in the plasma membrane that is involved in the innate immune response regulating, for example, chemotaxis in neutrophils and cytokine secretion in monocytes and macrophages. The intracellular adenine nucleotides ADP-ribose (ADPR) and 2′-deoxy-ADPR (2dADPR) activate the channel, in combination with their co-agonist Ca 2+ . Interestingly, activation of human TRPM2 (hsTRPM2) by 2dADPR is much more effective than activation by ADPR. However, the underlying mechanism of the nucleotides' differential effect on the channel is not yet fully understood. In this study, we performed whole-cell patch clamp experiments with HEK293 cells heterologously expressing hsTRPM2. We show that 2dADPR has an approx. 4-fold higher Ca 2+ sensitivity than ADPR (EC50 = 190 and 690 nM). This allows 2dADPR to activate the channel at lower and thus physiological intracellular Ca 2+ concentrations. Kinetic analysis of our data reveals that activation by 2dADPR is faster than activation by ADPR. Mutation in a calmodulin binding N-terminal IQ-like motif in hsTRPM2 completely abrogated channel activation by both agonists. However, mutation of a single amino acid residue (W1355A) in the Cterminus of hsTRPM2, at a site of extensive inter-domain interaction, resulted in slower activation by 2dADPR and neutralized the difference in rate of activation between the two agonists. Taken together, we propose a mechanism by which 2dADPR induces higher hsTRPM2 currents than ADPR by means of faster channel activation. The finding that 2dADPR has a higher Ca 2+ sensitivity than ADPR may indicate that 2dADPR rather than ADPR activates hsTRPM2 in physiological contexts such as the innate immune response.